THE EFFECT OF IMPLEMENTING THE DRILL LEARNING METHOD ASSISTED WITH PUZZLE MEDIA ON STUDENTS’ MATHEMATICS LEARNING OUTCOMES - Nur Hijrah Ramadhani Baharuddin; M. Shabir U; Suharti, Suharti; Andi Halimah; Baharuddin (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
This study aims to determine the effect of the Drill learning method assisted by puzzle media on the mathematics learning outcomes of grade III students of SD No. 21 Bulukunyi, Takalar Regency. The study used a quantitative approach with a quasi-experimental design with a nonequivalent control group design type, involving two groups, namely class IIIA as the experimental class and class IIIB as the control class. The research instruments were in the form of learning outcome tests and checklists, which had gone through validity and reliability tests. Data analysis used an independent sample t-test to ensure that the data was normal and homogeneous. The results of the study showed that the application of the Drill learning method assisted by puzzle media had a significant effect on improving students’ mathematics learning outcomes. Thus, the drill method assisted by puzzle media can be an effective, innovative method to improve mathematics learning outcomes, especially in building concrete conceptual understanding.